2016
DOI: 10.1017/s0376892916000059
|View full text |Cite
|
Sign up to set email alerts
|

The consumption of wild meat in Madagascar: drivers, popularity and food security

Abstract: SUMMARYThe role of wild meat for subsistence or as a luxury good is debated. We investigated the role of wild meat in food security in Madagascar, where consumption is poorly understood in urban areas and at regional scales. Using semi-structured interviews (n = 1339 heads-of-households, 21 towns), we aimed to: (1) quantify the amount and purpose of, (2) understand the drivers of, and (3) examine changes in wild meat consumption. Few respondents preferred wild meat (8 ± 3%) but most had eaten it at least once … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…Economic opportunities include farming for rice and cash crops, ranching, ecotourism (near the main park entrance, eastern side of the park) (Gezon, ; Walsh, ), and the extraction of natural resources including the mining/sale of sapphires (near the north‐eastern section of the park, Walsh, ), harvest/sale of wood (Gudiel et al ., ), wild meat (Reuter et al ., ), and other NTFPs (medicinal plants, K. E. Reuter, pers. obs.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Economic opportunities include farming for rice and cash crops, ranching, ecotourism (near the main park entrance, eastern side of the park) (Gezon, ; Walsh, ), and the extraction of natural resources including the mining/sale of sapphires (near the north‐eastern section of the park, Walsh, ), harvest/sale of wood (Gudiel et al ., ), wild meat (Reuter et al ., ), and other NTFPs (medicinal plants, K. E. Reuter, pers. obs.).…”
Section: Methodsmentioning
confidence: 99%
“…Improved understanding of the drivers of natural resource use are needed in biodiversity‐rich areas, like Madagascar, that are experiencing rapid anthropogenic habitat change. In Madagascar, 90% of the population lives on <2 USD per day (World Bank, ) and natural resources wood (Innes, ), non‐timber forest products (NTFPs; Novy, ), mining (Walsh, ), and animals (Golden et al ., ) – are regularly extracted for personal use, cultural reasons, and economic gain (Reuter et al ., ,b). Extraction occurs legally and illegally, inside and outside protected areas (Reuter et al ., ,b), involving people of different ethnicities, religions, and socioeconomic backgrounds (Walsh, ; Innes, ; Golden et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Borgerson et al [35] have shown that most children in the households of wildlife hunters were malnourished. Bushmeat was often the only accessible food for these families, and under these circumstances, it is no wonder that hunters are lured into commercial bushmeat chains that provision hotel and restaurants with lemur meat as a prestige food [36]. Another study in Madagascar has predicted that the rate of childhood anaemia would increase 29% if access to bushmeat, including bat and lemur meat, was restricted, predominantly affecting the poorest households that could not afford to purchase meat from domesticated animals [37].…”
Section: The Bushmeat-euphoriamentioning
confidence: 99%
“…Most of these studies have used PA management effectiveness (PAME) evaluations, as proxies for management input and quality which uses an ordinal scoring covering various aspects of PA management . Yet, the country struggles with high poverty levels and an unstable political environment, putting high pressures on the remaining forests, both through illegal high-value wood logging, shifting cultivation for subsistence farming, forest degradation due to charcoal production, overharvesting of vertebrates for bushmeat or trade and, more recently, escalating mining pressures (Allnutt, Asner, Golden, & Powell, 2013;Cabeza, Terraube, Burgas, Temba, & Rakoarijaoana, 2019;Reuter, Randell, Wills, & Sewall, 2016;Scales, 2014). We do this using a case-study of Madagascar's PAs, using avoided deforestation as a proxy for PA impact, and management data from PAME evaluations conducted by the National Parks authority.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, Madagascar has become a recipient of significant biodiversity aid funding (Miller, Agrawal, & Roberts, 2013). Yet, the country struggles with high poverty levels and an unstable political environment, putting high pressures on the remaining forests, both through illegal high-value wood logging, shifting cultivation for subsistence farming, forest degradation due to charcoal production, overharvesting of vertebrates for bushmeat or trade and, more recently, escalating mining pressures (Allnutt, Asner, Golden, & Powell, 2013;Cabeza, Terraube, Burgas, Temba, & Rakoarijaoana, 2019;Reuter, Randell, Wills, & Sewall, 2016;Scales, 2014).…”
Section: Introductionmentioning
confidence: 99%